Clinical and histopathological study of 279 dentigerous cysts in 192 dogs (2012–2022) - Vesterinen, Senni; Lönnberg, Laura; Junnila, Jouni J. T.; Luotonen, Niina; Kuntsi, Helena (Frontiers in Veterinary Science, 2024)
Unerupted teeth in dogs are fairly common and may develop an odontogenic cyst that causes destruction of the surrounding bone and affect adjacent teeth. We analyzed histological reports of cysts associated with unerupted teeth in a large population of dogs. Medical records and histopathological results of cysts associated with unerupted teeth were evaluated from all dogs treated at a private referral veterinary dental clinic over a 10-year period (2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022). A total of 192 dogs with 279 cysts associated with one or more unerupted teeth were included in the study. Brachycephalic breeds were overrepresented. The most affected were Tibetan Spaniels with 58 dogs (30%) and Boxers with 48 dogs (25%). The most common affected tooth was the mandibular first premolar tooth with 238 (84%) cysts. Of the total of 279 cysts, 208 (75%) were histopathologically examined. None of the cysts examined contained malignant changes. Based on these 208 cysts, the probability of finding a cyst with malignant changes in a population of dogs is 0-1.4% (confidence interval 95%).